Real-Time 262-Mb/s Visible Light Communication With Digital Predistortion Waveform Shaping - Weishu Xu; Min Zhang; Dahai Han; Zabih Ghassemlooy; Pengfei Luo; Yongjian Zhang (IEEE Photonics Journal, 2018)
A digital predistortion waveform shaping scheme combined with a blue filter is proposed to optimize both the rise and fall times of a light-emitting diode (LED) and the optical receiver current of the signal of the real-time visible light communication (VLC) system. The proposed scheme is implemented on a field-programmable gate array (FPGA) and a digital-to-analog converter based test bed, which is flexible and reconfigurable by programming the FPGA to match different LED characteristics and varied data rates. A 262-Mb/s non-return-to-zero on-off keying modulation based real-time VLC link with a bit error rate of less than $1.0× 10^{-6}$ is achieved over a transmission distance of 5.0 m, which uses a single white phosphorous LED with a limited power of 0.1 W.